Effect of Silver Diamine Flouride and Potassium Iodide Treatment on Microhardness - Alulaiyan, Mohammed. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2019.; Submitted to the Dept. of Pediatric Dentistry.; Advisor: Cheen Loo.; Committee: Yoon Kang, Jerry Swee, and Matthew Finkelman.; Keyword: Dentistry.